Identifying data sources for a national population-based registry: the experience of the Spanish Rare Diseases Registry. Issue 3 (March 2015) - Zoni, A.C.; Domínguez Berjón, M.F.; Barceló, E.; Esteban Vasallo, M.D.; Abaitua, I.; Jiménez Villa, J.; Margolles Martins, M.; Navarro, C.; Posada, M.; Ramos Aceitero, J.M.; Vázquez Santos, C.; Zurriaga Llorens, O.; et al.
Highlights: Population-based disease registries are key instruments for rare diseases (RD) research. The Spain Rare Disease Registry (Spain-RDR) is an IRDiRC project aimed at creating a national population-based RD registry. This paper provides a comprehensive description of rare disease data sources in Spain. The estimated number of RD that may be linked to the Spain-RDR is around 1200. The Spain-RDR will contribute to improving the planning and management of these diseases.